The Effectiveness of Using Herbal Packages (VCO, Honey, Black Seed) as Alternative Treatment for Covid-19 in the Community - Safira Bela Annisa; Fahrun Nur Nur Rosyid (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Covid-19 is an infectious disease that can cause death. Herbal medicines have anti-inflammatory properties associated with cytokine storm development. This means it prevents increases in inflammatory mediators, erythrocyte sedimentation rate (ESR), interleukin (IL)-6, and C-reactive protein (CRP). This study aimed to determine the effectiveness of using herbal packages (VCO, honey, Black Seed) as an alternative treatment for Covid-19 in the community. This research is a Quasi-experimental quantitative study with a control group design (control group design) Pretest-Posttest Control Group Design design. This research was conducted in Boyolali Regency. This research was conducted from October 2022 - January 2023. The population in this study were individuals with a history of Covid-19 disease in Boyolali Regency, 82 in December 2022. The research sampling technique was simple random sampling. The research sample consisted of 46 people consisting of the intervention group of 23 respondents and the control group of 23 respondents. The research instruments were questionnaires, observation forms, and other forms, and measurements were made using a sphygmomanometer, oxymeter, and thermometer. Analysis of bivariate analysis research data using the Paired Sample t-test, Independent Sample t-test, and the help of the SPSS software computer application. The analysis results obtained the p-value for saturation measurement in the treatment group, namely p = 0.024 <0.05, and for temperature measurements, p = 0.014 <0.05, so it can be concluded that herbal packages are effective as an alternative treatment for the Covid-19 virus in the community. It is known that most respondents in the treatment group felt better after consuming the herbal package. Herbal packages have proven effective in dealing with the sequelae caused by Covid-19 and are effective as a companion to the treatment of Covid-19 patients. Keywords: Black Seed, Covid-19, Effectiveness, Honey, Virgin Coconut Oil